2011
DOI: 10.1002/icd.758
|View full text |Cite
|
Sign up to set email alerts
|

Corporal Punishment and Child Behavioural and Cognitive Outcomes through 5 Years of Age: Evidence from a Contemporary Urban Birth Cohort Study

Abstract: This study examined the prevalence and determinants of spanking of children at 3 years-of-age, and the associations between spanking and externalizing behavior and receptive verbal ability at age 5. Overall, we find maternal spanking rates of 55.2% and paternal rates of 43.2% at age 3. Mothers facing greater stress and those who spanked earlier are more likely to spank at age 3, whereas those who report a supportive partner during pregnancy and those who were not U.S. born were less likely to spank. Mothers an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
3
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(88 citation statements)
references
References 43 publications
5
78
3
1
Order By: Relevance
“…In particular, a large and growing literature points toward an association between spanking and higher levels of aggression among children. 2,[7][8][9][10][11][12][13] However, there remain some limitations in the research to date. 14,15 First, few studies have used longitudinal samples to address the temporal sequencing of spanking and child outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In particular, a large and growing literature points toward an association between spanking and higher levels of aggression among children. 2,[7][8][9][10][11][12][13] However, there remain some limitations in the research to date. 14,15 First, few studies have used longitudinal samples to address the temporal sequencing of spanking and child outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…[16][17][18] Two studies have examined spanking and cognitive outcomes prospectively but only in very young children. Berlin et al 7 found links between spanking and early child Bayley scores in a large sample of lowincome preschoolers and toddlers, and MacKenzie et al 10 found evidence of associations between early spanking and lower child vocabulary scores at age 5.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…35) Researchers are also finding that physical punishment is linked to slower cognitive development and receptive vocabulary, and poorer academic achievement. 36,37) These findings come from large longitudinal studies that control for a wide range of potential confounders. 38) Intriguing results are now emerging from neuroimaging studies that suggest physical punishment may reduce the volume of grey matter in the prefrontal cortex 39) and may cause alter-ations in the dopaminergic regions associated with vulnerability to drug and alcohol abuse.…”
Section: The New Millenium: Addressing Causation and Broadening Focusmentioning
confidence: 99%